Analisis Perhitungan Teknis Brake Cylinder 10 inch dan 12 inch Pada Gerbong Terbuka (Studi Kasus : Gerbong Terbuka Di Balai Yasa Surabaya Gubeng) - Wahjono, Hari Boedi; Zulkarnain, Akbar; Rukai, Royyan (Politeknik Perkeretaapian Indonesia Madiun, 2018)
This study was structured with the aim to determine the effect of changing the brake cylinder from 10 inches to 12 inches in the Open Carriage, because this Open Carriage is the only car that has two different brake cylinders from the other Carriage. The study was conducted by calculating the percentage of braking on the use of 10-inch and 12-inch type brake cylinders on the Open Carriage used at Balai Yasa Surabaya Gubeng. Calculate the working time and release time on the brake cylinder with a size of 10 inches and 12 inches of pressure 0.4 to 3.8 kg / cm2. Calculates the braking distance assuming the type of locomotive and the number of carriages drawn are the same. The study produced work time and release time that varied results, namely faster work time on BC 12 inch and faster release time on BC 10 inch. The results of the braking percentage that has been obtained from calculations with the standard braking percentage is 40% <l £ 120%. From the standard determined according to UIC, the use of a 10 inch brake cylinder does not meet the requirements of the braking percentage calculation when the load is full, and for a 12 inch brake cylinder can meet the specified requirements. The results of the percentage of brake block pressure that has been obtained from calculations with the standard braking percentage is 30% <þ 85%. From the standard determined according to UIC, the use of a 10 inch brake cylinder does not meet the requirements in the calculation of the percentage of the full charge brake block pressure, while for a 12 inch brake cylinder it meets. The braking distance obtained from the calculated simulation results with predetermined factors results in the braking distance for BC 12 inch being closer than that using 10 inch BC. To improve the results of this study it is necessary to test the brake cylinder components dynamically.